Effects of timing of complementary food introduction on childhood food allergy development: A modified role of ambient air pollution exposure. (1st March 2023) - Lu, Chan; Zhang, Xin; Liu, Qin; Li, Qin; Norbäck, Dan; Deng, Qihong
Abstract: Background: Food allergy increased in the recent years causing heavy disease burden worldwide, yet the unique factors for the second-wave allergy epidemic since a rise of allergic diseases are unclear. Objective: To examine the impact of introduction timing of complementary foods on childhood food allergy and whether ambient air pollution modify this association. Methods: A retrospective cohort study of 2, 598 preschoolers was conducted at 36 kindergartens at Changsha of China during 2011–2012. A standard questionnaire was developed to survey each preschooler's introduction timing of complementary foods, food allergy, and home environments. Each subject's exposure to ambient air pollutants including PM10, SO2, and NO2 was estimated for pregnancy and postnatal period. Association between food allergy and introduction timing of complementary foods as well as its modification by ambient pollution were evaluated by multiple logistic regression model. Results: Childhood total food allergy (14.6%) was significantly positively associated with early introduction to fruit or vegetable before 3 months with OR = 1.97 (1.25–3.11), especially for egg and milk allergies. Food allergy was also significantly associated with NO2 exposure in pregnancy especially during the 1st trimester with ORs (95% CI) = 1.24 (1.00–1.54) and 1.27 (1.03–1.58) and postnatal period with OR of 1.30 (1.01–1.66) respectively for per IQR increase in their exposure. We observed that living near traffic-main road and other areas significantly increased food allergy risk of early introduction of fruit and vegetable. We further detected that early introduction of milk powder or porridge significantly decreased the risk of food allergy at the condition of light outdoor air pollution exposure during postnatal period. Sensitivity analysis showed that children living at urban area, male sex, younger age, and having breast-feeding were more susceptible to the effect of early introduction of fruit and vegetable on food allergy. Conclusion: Our study indicates that the role of introduction timing of complementary foods on food allergy could be adjusted by air pollution exposure level, which may partly explain the second-wave allergy epidemic and provide a potential preventive strategy. Graphical abstract: Image 1 Highlights: Childhood food allergy was associated with early introduction of fruit and vegetable before 3 months. Food allergy was related to NO2 exposure in pregnancy especially 1st trimester and postnatal stage. Living near traffic area increased food allergy risk of early introduction of fruits and vegetables. Low air pollution increased protective effect of early introduction of food allergens on food allergy. Air pollution modified effect of solid food addition at different time on food allergy development.